Application of γ-PGA as the primary carbon source to bioremediate a TCE-polluted aquifer: A pilot-scale study. (December 2019) - Luo, S.G.; Chen, S.C.; Cao, W.Z.; Lin, W.H.; Sheu, Y.T.; Kao, C.M.
Abstract: The effectiveness of using gamma poly-glutamic acid (γ-PGA) as the primary carbon and nitrogen sources to bioremediate trichloroethene (TCE)-contaminated groundwater was studied in this pilot-scale study. γ-PGA (40 L) solution was injected into the aquifer via the injection well (IW) for substrate supplement. Groundwater samples were collected from monitor wells and IW and analyzed for TCE and its byproducts, geochemical indicators, dechlorinating bacteria, and microbial diversity periodically. Injected γ-PGA resulted in an increase in total organic carbon (TOC) (up to 9820 mg/L in IW), and the TOC biodegradation caused the formation of anaerobic conditions. Increased ammonia concentration (because of amine release from γ-PGA) resulted in the neutral condition in groundwater, which benefited the growth of Dehalococcoides . The negative zeta potential and micro-scale diameter of γ-PGA allowed its globule to distribute evenly within soil pores. Up to 93% of TCE removal was observed (TCE dropped from 0.14 to 0.01 mg/L) after 59 days of γ-PGA injection, and TCE dechlorination byproducts were also biodegraded subsequently. Next generation sequence (NGS) analyses were applied to determine the dominant bacterial communities. γ-PGA supplement developed reductive dechlorinating conditions and caused variations in microbial diversity and dominant bacterial species. The dominant four groups of bacterial communities including dechlorinating bacteria, vinyl chloride degrading bacteria, hydrogen producing bacteria, and carbon biodegrading bacteria. Graphical abstract: Image 1 Highlights: γ-PGA can provide substrate and NH4 + continuously and enhance TCE dechlorination. Release of amine from γ-PGA could produce ammonia for acidification control. γ-PGA has a small diameter, which prevents soil clogging after injection. γ-PGA causes variations in microbial diversity and dominant bacterial species.